2008
DOI: 10.1097/mbc.0b013e32830ef90c
|View full text |Cite
|
Sign up to set email alerts
|

Rotational thromboelastography for monitoring of fibrinogen concentrate therapy in fibrinogen deficiency

Abstract: To characterize a functional assay for circulating fibrinogen based on rotational thrombelastography. Maximum clot firmness was determined by rotational thrombelastography in normal human plasma pool, fibrinogen-deficient plasma pool, normal whole blood, and individual plasma samples from 17 patients with fibrinogen deficiency. Plasma samples spiked with varying concentrations of exogenous fibrinogen were also measured. Results were compared with enzyme-linked immunosorbent assay and Clauss assay. The impact o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
46
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(56 citation statements)
references
References 33 publications
9
46
0
1
Order By: Relevance
“…Rotational thrombelastography (ROTEM) yields information not only about the fibrin clot formation but also measures fibrin-platelet interaction, clot firmness and fibrinolysis and may provide a more comprehensive impression of the coagulation process under fibrinogen replacement [26].…”
Section: Discussionmentioning
confidence: 99%
“…Rotational thrombelastography (ROTEM) yields information not only about the fibrin clot formation but also measures fibrin-platelet interaction, clot firmness and fibrinolysis and may provide a more comprehensive impression of the coagulation process under fibrinogen replacement [26].…”
Section: Discussionmentioning
confidence: 99%
“…An advantage of thrombelastometry is that the method allows determination of the combined effects of thrombocytopenia and hypofibrinogenaemia. It is interesting, in this regard, that thrombelastometry was recently demonstrated to be the most reliable method of identifying patients with afibrinogenaemia, hypofibrinogenaemia, and dysfibrinogenaemia [10].…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, Kalina et al [32] demonstrated that the assessment of MCF by FIBTEM and EXTEM provided a consistent and more predictable response to fibrinogen administered in vitro to patients with afibrinogenemia, hypoFI or dys-FI, than the assessment of fibrinogen concentration by the von Clauss or ELISA method. In particular, while patients with dysFI demonstrated a good correlation between added fibrinogen and higher MCF readings, the response to fibrinogen spiking was found to be blunted by interactions with abnormal fibrinogen structure when using the von Clauss method.…”
Section: Patientsmentioning
confidence: 99%